Characterization of the complete chloroplast genome of Cycas hongheensis (Cycadaceae), an endemic species in the red river region of China. Issue 12 (2nd December 2021) - Wu, Li-Xin; Wang, Yue-Hua; Gong, Xun
Abstract: In this study, we determined the complete chloroplast genome of Cycas hongheensis (Cycadaceae), one of the first-class protected plants in China. The chloroplast genome is 162, 048 bp in length with 133 genes, including 87 protein-coding genes, eight ribosomal RNA genes, and 37 transfer RNA genes. The overall GC content is 39.4%. Phylogenomic analysis showed that C. hongheensis as sister to all other Cycas species that with reported chloroplast genomes. The chloroplast genome of C. hongheensis reported here will contribute to further comparative chloroplast genome of Cycads and helpful to study the phylogeography of Cycadaceae.